Perceived stress among Malay caregivers of children with learning disabilities in Kelantan - Siti Nor Ismalina Isa,; Ismarulyusda Ishak,; Azriani Ab Rahman,; Nur Zakiah Mohd Saat,; Normah Che Din,; Syarif Husin Lubis,; Muhammad Faiz Mohd Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Parents or caregivers of children with learning disabilities have been shown to experience increases in stress and greater negative caregiving consequences than those with typically developing children. The current study sought to assess the perceived stress among Malay caregivers of children with learning disabilities in Kelantan. The Malay version of Perceived Stress Scale 10 items was administered to a sample of 40 caregivers of children with learning disabilities who were registered to five Pusat Pemulihan Dalam Komuniti (PDK) in Kelantan. Higher scores indicate higher levels of stress. The caregivers had mean age of 47.68 (SD = 9.18) years old, of whom 90% were fathers or mothers. Ninety percent of them were married, majority were unemployed or housewives and had secondary school education. The majority of children with learning disabilities were males and half of them were Down Syndrome children. The mean total Perceived Stress Scale score of the caregivers was 16.77 (SD = 5.74). There were no significant associations between total perceived stress score and any of the independent variables. The mean total perceived stress score showed that the perceived stress level was in the category of slightly higher than average and health concern level was high, while the average stress level was between score of 12 to 15. In conclusion, this result indicated that the caregivers had slightly higher levels of stress than the average score, and might increase susceptibility to stress-induced illness.